Local Wisdom And Religious Moderation: Synergy For Peace - Karyoto; Rahmat Hidayatullah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to analyze the role of local wisdom and religious moderation as important elements in building peace in a multicultural society. Local wisdom, which includes norms, values ​​and traditions passed down from generation to generation, has a function in creating social harmony and community cohesion. On the other hand, religious moderation encourages a balanced, tolerant approach to religion and rejects extremism, so that it can buffer conflicts between religious groups. Using a qualitative approach with descriptive methods, this research collects data from literature studies and field observations in communities that apply local wisdom in everyday life. A qualitative approach was chosen because it allows researchers to explore a deep understanding of social phenomena through comprehensive interpretation. Research findings show that the synergy between local wisdom and religious moderation has the potential to be a solution to religious-based conflicts, as well as playing an important role in strengthening social cohesion and minimizing potential conflicts caused by differences in religious views. This synergy, if implemented consistently, will not only maintain social stability but also contribute to the development of a peaceful, just and inclusive society.